2015
DOI: 10.1039/c4dt03960b
|View full text |Cite
|
Sign up to set email alerts
|

A phosphomide based PNP ligand, 2,6-{Ph2PC(O)}2(C5H3N), showing PP, PNP and PNO coordination modes

Abstract: A new class of PNP pincer ligands, pyridine-2,6-diylbis(diphenylphosphino)methanone, 2,6-{Ph2PC(O)}2(C5H3N) (1) (hereafter referred to as "bis(phosphomide)"), was prepared by the reaction of picolinoyldichloride with diphenylphosphine in the presence of triethylamine. The bis(phosphomide) 1 shows symmetrical PNP, unsymmetrical PNO and simple bidentate PP coordination modes when treated with various transition metal precursors. The reaction between 1 and [Ru(p-cymene)Cl2]2 in a 1 : 1 molar ratio yielded a binuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 97 publications
(6 reference statements)
5
23
0
Order By: Relevance
“…We have confirmed that [Pt(L)(Eind 2 -BPEP)] complexes (2)(3)(4)(5)(6) possess ad istinct tendency to adopt as quare-planar configuration aroundt he Pt center,i rrespectiveo ft he electronic properties of L. Although the strong p-acceptor CO ligand produces flexibility towards distortion, the optimized structure of model complex 6 sm as well as the X-ray structure of complex 6 showedt hat planarity was preserved aroundt he Pt center.T he highly adaptable electronics tructure of the Eind 2 -BPEP ligand and the characteristic d 9 s 1 electron configurationo fP tt hat arise from relativistic effectsh ave emerged as the origins of the unusual coordination structure. p-Accepting properties of Ls ignificantly affect the HOMO levels, which led to remarkable color variationso ft he complexes in the near-infrared region.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…We have confirmed that [Pt(L)(Eind 2 -BPEP)] complexes (2)(3)(4)(5)(6) possess ad istinct tendency to adopt as quare-planar configuration aroundt he Pt center,i rrespectiveo ft he electronic properties of L. Although the strong p-acceptor CO ligand produces flexibility towards distortion, the optimized structure of model complex 6 sm as well as the X-ray structure of complex 6 showedt hat planarity was preserved aroundt he Pt center.T he highly adaptable electronics tructure of the Eind 2 -BPEP ligand and the characteristic d 9 s 1 electron configurationo fP tt hat arise from relativistic effectsh ave emerged as the origins of the unusual coordination structure. p-Accepting properties of Ls ignificantly affect the HOMO levels, which led to remarkable color variationso ft he complexes in the near-infrared region.…”
Section: Resultssupporting
confidence: 74%
“…All manipulations were carried out under an itrogen atmosphere. Eind 1,3,3,5,5,7,2,3,5,6, [3] and [Pt(cod) 2 ] [12] were prepared according to literature procedures. The other chemicals were obtained from commercial suppliers and used without purification.…”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The coordination chemistry of such “phosphomide” ligands is, nonetheless, scant and largely restricted to groups 6–8 (Cr, Mo,, W, Mn, Re, Fe, Ru) with an emphasis on the first‐row metals. A limited range of group 9 complexes has been described with “Cp′RhCl 2 ” (Cp′ = Cp, Cp*) and “Cp*IrCl 2 ” fragments; however, trans ‐Rh(CO)(L) 2 Cl (L = PH 2 {C(O)Me}, PPh 2 {C(O)C 7 F 15 }, PPh 2 {C(O) p ‐An}) and [Rh{κ 2 ‐ P , P ‐C 6 H 3 N{PC(O)PPh 2 } 2 ‐2,6}Cl][13a] are the only low‐valent group 9 complexes known.…”
Section: Introductionmentioning
confidence: 99%